2008
DOI: 10.1103/physrevlett.100.196804
|View full text |Cite
|
Sign up to set email alerts
|

Electron-Vibration Interaction in Single-Molecule Junctions: From Contact to Tunneling Regimes

Abstract: Point contact spectroscopy on a H(2)O molecule bridging Pt electrodes reveals a clear crossover between enhancement and reduction of the conductance due to electron-vibration interaction. As single-channel models predict such a crossover at a transmission probability of tau=0.5, we used shot noise measurements to analyze the transmission and observed at least two channels across the junction where the dominant channel has a tau=0.51 +/- 0.01 transmission probability at the crossover conductance, which is consi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
196
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 172 publications
(207 citation statements)
references
References 27 publications
(43 reference statements)
5
196
3
Order By: Relevance
“…The step feature indicates on a vibration which is excited by the transport electrons having an energy of 40 meV [12]. The conductance enhancement is typical for inelastic electron tunneling spectroscopy, as expected for vibration excitation at zero bias conductance below 0:5G 0 [14,15]. In order to accurately determine the associated vibration energy, 250 differential conductance spectra were collected for junctions having a zero bias conductance of 0:05-0:4G 0 , resulting in the energy histogram presented in Fig.…”
mentioning
confidence: 92%
“…The step feature indicates on a vibration which is excited by the transport electrons having an energy of 40 meV [12]. The conductance enhancement is typical for inelastic electron tunneling spectroscopy, as expected for vibration excitation at zero bias conductance below 0:5G 0 [14,15]. In order to accurately determine the associated vibration energy, 250 differential conductance spectra were collected for junctions having a zero bias conductance of 0:05-0:4G 0 , resulting in the energy histogram presented in Fig.…”
mentioning
confidence: 92%
“…The appearance of this common peak is rather surprising specifically for Pt/ H 2 and Pt/ H 2 O for which it has been demonstrated that the conductance at the 1G 0 peak in the histogram is carried dominantly by a single conductance channel. 4,6 According to the Landauer equation G = ͚ i G 0 T i , where T i is the ith transmission probability for an electron to cross the junction. For a single conductance channel, G = G 0 T, thus the channel is fully open ͑T =1͒ at G =1G 0 .…”
Section: Conductance Histogramsmentioning
confidence: 99%
“…9 The direct binding of simple molecules to the electrodes offers a valuable opportunity to explore some of the central questions related to electron transport through molecular junctions. 6,7,10 The high conductivity and the relatively simple electronic and atomic structure of such junctions permit adapting experimental techniques that were originally developed for atomic point contacts ͑e.g., measurements of shot noise, 11,12 conductance fluctuations, 4,13 and subgap structure in superconducting contacts 14,15 ͒ and explore the effect of different manipulations such as junction stretching and isotope substitution on inelastic spectroscopy. 10,16,17 This variety of experimental tools extends the number of observed properties available for research.…”
Section: Introductionmentioning
confidence: 99%
“…It is generally admitted that in tunneling, the excitation of a vibration mode leads to opening an inelastic channel for conduction, hence increasing the conductance. [18][19][20][21] However, early model calculations predicted that when a molecular resonance overlaps the Fermi level of the substrate, IETS could also give rise to decreases in conductance. 18 Up to now, the O 2 ͓001͔ is the only example, where such decreases in conductance have been observed experimentally.…”
Section: Introductionmentioning
confidence: 99%